Job quality in turbulent times: An update of the European Job Quality Index - Agnieszka Piasna (European Trade Union Institute (ETUI), 2023)
This paper presents the latest results of the European Job Quality Index, updated with 2021 data, and compares the relative performance of EU countries on the Index over time. The study makes both a conceptual and an empirical contribution, by proposing an approach to measuring job quality suitable for comparative crossnational research, as well as for guiding policy by clearly indicating the desired direction for change. Moreover, the study reviews evidence in support of the synergy between job quantity and quality, and also reveals the positive relationship between collective interest representation and several other dimensions of job quality. Finally, it illustrates the unequal distribution of job quality across different groups of the European workforce.
Keywords: 330; Arbeitsbedingungen; Vergleich; EU-Staaten